Extraordinary influence how great leaders bring out the best in others - Irwin, Tim 1949- (Gildan, 2018)
The age-old question for every leader---how do we bring out the best in those we lead? Anyone who has run a company, raised a family, lead an army, or coached a team struggles to find the key to help others excel and realize their potential. It is surprising how often we resort to criticism vs. an approach that actually results in a better worker and a better person.
Online resource; title from title details screen (OverDrive, viewed June 6, 2018)
Keywords: Transformational leadership; Employees -- Coaching of; Employees -- Rating of; Personnel management; Personnel Management; Leadership transformationnel; Personnel; Direction; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Employees; Coaching of; Employees; Rating of; Downloadable audio books; Audiobooks; Livres audio